Developing a Theater Program for Inner Self-Learning: Enhancing Male Juvenile Observation and Protection Training Centers' Self-Esteem - Sophonsuwapap, Paiboon; Makmee, Pattrawadee; Aerarunchot, Suwadee; Ruangtip, Parinya (Journal of Fine and Applied Arts Khon Kaen University, 2025)
This research article presents the experience of Developing a Theater Program for Inner Self-Learning: Enhancing Male Juvenile Observation and Protection Training Centers' Self-Esteem. It is research and development. The research methodology used qualitative and quantitative methods and purposive sampling in the Male Juveniles Observation and Protection Training Centers in District 4, Khon Kaen Province. The program development process has three steps: 1) the process of analyzing problem conditions and searching for information on organizing youth development programs; 2) developing a prototype program (D1) to try out and develop into a prototype program for the second time (D2) and 3) Steps in implementing the D2 program and improving the program prototype until it is complete. The research results were a drama program for learning one's inner self to Self-Esteem, consisting of 8 sets of drama, art, and group activities. The activity format is characterized as "playing" with the feelings of youth. "It is the bringing of the torso-body. Moreover, feelings - go play - go live - learn consciously" so youths can find meaning in living and develop their inner selves.